Quantitative determination on biodegradation of PAHs by bacteria from oil sludge / Norhafiza Abdul Ghani - Abdul Ghani, Norhafiza (2008)
The biodegradability of petroleum waste product was evaluated using oil sludge taken from Exxon Mobil petroleum refiner y treatment plant in Kerteh, Terengganu. This study was a further extension of studies conducted by Dzulkafli (2007) where the qualitative analysis was established. The analysis involves the utilization of bacterial strains most effective in PAHs degradation as classified by Dzulkafli (2007). The PAHs adopted were phenanthrene, anthracene and dibenzothiophene which were used as source of carbon. PCR and DNA Sequencing were conducted to confirm the identity of bacterial strain classified by Dzulkafli (2007). These molecular technique s provide s up to 90% accuracy of identification. Using these techniques these three strains identified belong to genus of Pseudomonas namely; Uncultured Pseudomonas sp. clone 2-A, Pseudomonas Stutzeri strain HS-D36 and Pseudomonas Stutzeri strain LS40 1. Turbidity test was conducted for growth rates of each strain. Pseudomonas Stutzeri strain HS-D36 indicated the highest growth rates followed by Uncultured Pseudomonas sp. clone 2-A and Pseudomonas Stutzeri strain LS401. Identification of the most effective PAH degrading by bacterial strain was established by determining of average degradation rates. Anthracene proved to be the most degraded by these strains with the highest average degradation rate followed by phenanthrene and dibenzothiophene. While, Pseudomonas Stutzeri strain HS-D36 revealed to be the best strain in degrading PAHs, with the highest degradation followed by Uncultured Pseudomonas sp. clone 2-A and Pseudomonas Stutzeri strain LS401.